From Palace to Communities: A Case Study of the Classical Court Dance Inheritance in Yogyakarta City - Saearani, Muhammad Fazli Taib; Wibowo, Denny Eko (International Journal of Psychosocial Rehabilitation, 2025)
This article will discuss the development of the Classical Court Dance of Yogyakarta from its days of sole ownership by Keraton Ngayogyakarta Hadiningrat to the spreading of the art among common people. From the historical perspective, the impact of World War II was huge in the development of Classical Court Dance in Yogyakarta as it stopped all forms of an art from being actively performed. Therefore, the Keraton decided to move all its arts activities to Ndalem Purwadiningratan, a community that consisted of both nobility and commoners. Such action by the Keraton had changed the status of Classical Court Dance of Yogyakarta from belonging exclusively belonging only to the Keraton to also being part of the community outside of its walls including the commoners. Throughout the years, the Classical Court Dance of Yogyakarta has been preserved and now further flourishes amongst the members of the community. This article will explain: (1) How such the changes occurred; (2) How the dance was transformed during the shift; (3) Which communities helped preserve the Classical Court Dance of Yogyakarta today, and (4) Is there an impact to the people of Keraton, the original owners of this court dance?. Therefore, this article shows that the dialectics that occur between the two entities, namely the palace and the community have resulted in the inheritance of the classical dance of Yogyakarta which is distinguished in two ways; traditional and non-traditional, according to the context of the era. This also relates to their respective strategies both in formal and non-formal institutions in holding the greatness of Yogyakarta artistic identity through classical dance style of Yogyakarta.